The Impacts of Teacher’s Speech Styles in Teaching English to EFL Young Learners - Ningsi, Ira Syahya; Jabu, Baso; Salija, Kisman (Har Press Indonesia, 2022)
Teachers’ speech styles in teaching English to EFL young learners. In this study, there are two point are explored: (1) Teachers’ speech style in the classroom interaction and (2) The impacts of teachers’ speech style to EFL Young learners. This research applies descriptive qualitative method. This research was conducted at first grade of MTs Darul Huffadh Tuju-Tuju Kajuara Bone of 2021/2022 academic year. The participants of this study were a teacher and twenty-nine EFL young learners’ classroom. The data of this study were obtained from observation and interview. The result of this study indicate there are four teachers’ speech style that was applied in the classroom interaction are; formal style, casual style, consultative style, and intimate style. Where all these styles there are some impacts to EFL young learners are: first, students’ motivation the teacher used formal, casual, and consultative style. Students’ politeness the teacher used formal and consultative. Students’ trust the teacher used consultative and intimate style. The last, students’ respect the teacher applied intimate style. The findings of this study can be a reflection for English teachers and students in carrying out the learning process by using this speech style when teaching English, and can find more interesting learning methods.